2002
DOI: 10.1159/000071478
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Constitutive Nitric Oxide Production Increases the Severity of Lipopolysaccharide-Induced Sickness Behaviour: A Role for TNF-α

Abstract: Administration of bacterial lipopolysaccharide (LPS) to rodents induces hypophagia, body weight loss and hypolocomotion, a constellation of symptoms collectively referred to as ‘sickness behaviour’. We examined the role of the gaseous transmitter nitric oxide (NO) in mediating LPS-induced sickness behaviour in rats. Treatment with the non-selective NO synthase (NOS) inhibitor NG-nitro-L-arginine (L-NA) (20 mg/kg; i.p.) increased the severity of LPS-induced sickness behaviour in rats, suggesting that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
7

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 45 publications
0
8
0
7
Order By: Relevance
“…DY510, Minneapolis, USA). TNF-α is considered a biomarker of sickness behavior [35, 40] and depression [11]. BDNF levels were determined using a Promega kit (cat.…”
Section: Methodsmentioning
confidence: 99%
“…DY510, Minneapolis, USA). TNF-α is considered a biomarker of sickness behavior [35, 40] and depression [11]. BDNF levels were determined using a Promega kit (cat.…”
Section: Methodsmentioning
confidence: 99%
“…However, there are suggestions that constitutive nitric oxide does not act as mediator of LPS-induced sickness behavior but have a role in an inhibitory feedback manner to limit LPS-induced sickness behavior. It has been shown that only inhibitors of endothelial ni- tric oxide synthase (example, L-NA) increased the severity of LPS-induced sickness behavior while iNOS or nNOS inhibitors does not have the same properties [47]. Ribeiro et al, [26] provides further evidence to show that the synthesis of NO modulates changes in depressive-like and exploratory behaviors in mice.…”
Section: Discussionmentioning
confidence: 99%
“…This seems counter-intuitive because the behavioral effects of acute LPS treatment are mediated via type 1 pro-inflammatory cytokines (Bluthe et al, 2000a;Bluthe et al, 2000b;Connor et al, 2002). This seems counter-intuitive because the behavioral effects of acute LPS treatment are mediated via type 1 pro-inflammatory cytokines (Bluthe et al, 2000a;Bluthe et al, 2000b;Connor et al, 2002).…”
Section: Discussionmentioning
confidence: 99%